2012
DOI: 10.1007/s00411-012-0407-z
|View full text |Cite
|
Sign up to set email alerts
|

Karyopathological traits of thyrocytes and exposure to radioiodines in Belarusian children and adolescents following the accident at the Chernobyl nuclear power plant

Abstract: The Belarus-American (BelAm) Thyroid Study cohort consists of persons 0–18 years of age at the time of exposure to radioiodines from the 1986 Chernobyl nuclear power plant accident who have undergone serial thyroid screenings with referral for fine-needle aspiration biopsy (FNAB) using standardized criteria. We investigated thyrocyte nuclear abnormalities in cytological samples from FNABs in 50 BelAm subjects with thyroid nodules and 43 control patients from Leningrad, Russia, unexposed to Chernobyl fallout. N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…However, the combination of "tailed" nuclei and bridges appeared only after exposure to ionizing radiation [17,26,33,34,37]. This was also confirmed by studies in which the appearance of "tailed" nuclei and nucleoplasmatic bridges was observed in the thyroid cells of mammals, in various cell lines and in peripheral blood lymphocytes of liquidators of the Chernobyl accident [26,38,39]. The simultaneous appearance in the cells of nucleoplasmatic bridges and "tailed" nuclei under the influence of radiation is also a consequence of the pleiotropism of chromosomal aberrations arising as a result of double-strand DNA breaks.…”
Section: Nucleoplasmatic Bridgessupporting
confidence: 67%
See 1 more Smart Citation
“…However, the combination of "tailed" nuclei and bridges appeared only after exposure to ionizing radiation [17,26,33,34,37]. This was also confirmed by studies in which the appearance of "tailed" nuclei and nucleoplasmatic bridges was observed in the thyroid cells of mammals, in various cell lines and in peripheral blood lymphocytes of liquidators of the Chernobyl accident [26,38,39]. The simultaneous appearance in the cells of nucleoplasmatic bridges and "tailed" nuclei under the influence of radiation is also a consequence of the pleiotropism of chromosomal aberrations arising as a result of double-strand DNA breaks.…”
Section: Nucleoplasmatic Bridgessupporting
confidence: 67%
“…For the same reason, bridges can persist for decades in thyroid cells exposed to radiation, due to their low proliferative capacity. Thus, the stretched bridges are a more convenient biomarker of ionizing radiation in the cells of the follicular epithelium of the thyroid gland, although "tailed" nuclei are also observed in the thyrocytes [32]. "Tailed" nuclei "Tailed" nuclei represent a thin protrusion or outgrowth of the nucleus into the cytoplasmic space.…”
Section: Nucleoplasmatic Bridgesmentioning
confidence: 99%
“…Well-differentiated thyroid cancers are the most common endocrine tumors in children and adolescents. A significant increase in the incidence of thyroid cancers was observed in children following the nuclear reactor meltdown in Ukraine and those exposed to the atomic blasts in Japan [5,6].…”
Section: Resultsmentioning
confidence: 99%
“…The survival in children and adolescents is better than in adults. An increase in the incidence of thyroid cancer has been observed in children exposed to the fallout of the Chernobyl accident [5] especially in the age group of less than one year at the time of the explosion [4].…”
mentioning
confidence: 99%
“…Examples are the thoracic irradiation of radiation fibrosisprone C57BL/6 mice (5 or 12.5 Gy) which caused cyclic changes in IL-1a and TGF-b levels etc. in the lung for at least 6 months (Rubin et al 1995); bone marrow cells derived from whole-body irradiated mice with 4 Gy exhibited inflammatory conditions for 15 months after an irradiation (Rastogi et al 2012); intercellular bridges (a manifestation of cell divisions in dicentric-bearing cells) were observed in human thyroid biopsy samples about 20 years after the Chernobyl accident (estimated mean thyroid dose was 2.5 Gy: Nadyrov et al 2012); and finally the presence of increased levels of serum inflammatory markers was suggested in atomic-bomb survivors 50 years after their exposure to radiation (Hayashi et al 2012). In short, it seems possible that any step in the multistep processes involved in carcinogenesis may be affected by radiation-induced tissue injuries depending on the severity of the damage and its duration.…”
Section: The Strength and Duration Of Inflammatory Conditionsmentioning
confidence: 99%